ESTUDO COMPARATIVO DE REMOÇÃO DE FERRO E MANGANÊS DE SOLUÇÃO AQUOSA POR OZONIZAÇÃO SEGUIDA DE FILTRAÇÃO UTILIZANDO AREIA, ZEÓLITA E CARVÃO ATIVADO GRANULAR - Emboaba, Débora Garcia (2019)
Iron and manganese, which are often found in groundwater in the state of Paraná, can dramatically change the aesthetic and organoleptic characteristics of water, and cause inconvenient situations for its consumers. Thus, this problem requires the design of a specific efficient viable treatment to ensure the availability of quality water for the population to be supplied. Therefore, this study investigated the efficiency of ozonation and filtration in the treatment of water containing iron and manganese, regarding to the removal of color, turbidity, total iron and total manganese, comparing three types of filter materials. The study aimed to confirm if this kind of treatment allows that the concentrations of such parameters to suit the drinking water standard. First of all, in the optimization stage, two samples with different Fe/Mn proportions, A (1 mgFe L-1 + 4 mgMn L-1) and B (3 mgFe L-1 + 4 mgMn L-1), were submitted to three different pH scale (acid, neutral and alkaline), and it was ozonated under three levels of ozone (minimum, medium and maximum concentration produced by the apparatus), and each test was performed in triplicate. It was found that ozonation at neutral pH and minimum ozone level shows the best Mn oxidation results for both samples. Subsequently, new samples A and B were prepared, ozonized under the optimum conditions and submitted to filtration in three different granular media: sand, zeolite and granular activated carbon (GAC). The results showed that, for sample A, with any of the filter media tested, it was not possible to reach the potability standards of the evaluated parameters; in the other hand, for sample B, the three filter materials provided suitable treatment efficiency for the concentration of turbidity and iron to comply with the limits established by the legislation. Whereas, regarding to the apparent color and manganese, it was only possible to fit the maximum allowed value (VMP) when the sample was filtered in GAC. In this way, ozone has been confirmed as an excellent oxidant of soluble metals, once it does not require high alkalinity to act effectively, especially in waters with high concentrations of Fe and Mn, although occurring simultaneously. Sample B was favored by the treatment, due to the autocatalytic reactions caused by the metal oxides present in a larger quantity in this sample than in the sample A. Between zeolite, sand and granular activated carbon, this last one showed to be the best material support for filtration, although its greater efficiency in relation to the other materials was not statistically significant; and the proposed treatment system of ozonation followed by filtration is more advantageous for the treatment of water with higher concentrations of Fe and Mn